Modernizing Administrative Work in Algeria: A Reading in the Constraints - Khaled, Asma; Hedidane, Sabrina (Journal of Human Sciences, 2021)
Through this scientific contribution, the researchers seek to give a reading on the practical situation of the administrative reform process in Algeria and the obstacles that have hindered this process and prevented the actual embodiment of it.The two researchers conclude that the modernization processes that the public administration has undergone at the technical level remain dependent on the degree of, like other institutions, is a bi-technical, Rationalize the side and neglect the other side.